Two ethnicities one hyaluronic skin booster comparative: a case series - Domenico, Romano; Fayez, Hend; Rossi, Tiziana (Aesthetic Medicine, 2024)
Aim: to assess the safety and efficacy of Viscoderm® Hydrobooster (VH) in treating skin ageing signs on the face of 10 female subjects from Italy and Oman with diverse features in terms of phenotype, genetics and anthropometry. Methods: two specialists in aesthetic medicine, one from Italy and one from Oman, recruited 5 patients each between 35-65 years old. 1.1 ml of VH were injected during 2 sessions at 60-day intervals, with 0.02 to 0.05 ml of product at each point. Post-treatment evaluation was scheduled at 4 months from baseline, photos were taken before, after each session and at final visit. VAS score ranging from 0 to 10 was recorded after each treatment, physician’s and patient’s GAIS scores ranging from -3 to +3 were provided at second and final visit. Results: GAIS score at second treatment was 2 for 4 patients out of 10 and in 5 out of 10 physicians reports, and 1 in 5 patients and 5 clinicians' reports, with an average value of 1.3 and 1.5 as to patients and specialists, respectively. As for GAIS evaluations at final visit, 8 patients and 8 clinical reports indicate the maximum positive score, with an average value of 2.8 for both patients and specialists, with strong agreement and great satisfaction. Average VAS value reported at baseline was 5.3 (SD 0.94), average VAS score at second treatment decreased at 5 (SD 0.66). Conclusions: in all the cases presented in this study, despite the different ethnicity and ageing features, VH provided deep hydration, increased elasticity, and tissue restructuring, stretching both dynamic and superficial wrinkles, along with improvement of skin defects, such as acne scars, with an early clinical benefit.